2019
DOI: 10.1111/bju.14904
|View full text |Cite
|
Sign up to set email alerts
|

The surgical learning curve for endoscopic GreenLight™ laser enucleation of the prostate: an international multicentre study

Abstract: Objectives To investigate the effect of surgical experience on the perioperative outcomes of endoscopic GreenLight™ (Boston Scientific Corporation, Marlborough, MA, USA) laser enucleation of the prostate (GreenLEP). Subjects/Patients and Methods A multicentre retrospective study of the first patients treated with GreenLEP by six surgeons was conducted. For each patient, surgical experience was coded as the total number of procedures performed by the surgeons before the patient's operation. The learning curve w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 18 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Perhaps the most important factor in the difficulty of implementing a new surgical technique is the learning curve (LC) (Naspro et al., 2017). An understanding of the LC is crucial to determine how much surgical experience is required to provide reproducible outcomes (Khene et al, 2020). In aEEP, the LC tends to be steep, and according to a recent analysis, 50–60 cases were required to effectively perform enucleation; and efficient morcellation was also reported after 60 cases (Hueber & Zorn, 2013; Jeon et al., 2019; Kampantais et al., 2018; Khene et al, 2020).…”
Section: Multiple Energy Sources and Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the most important factor in the difficulty of implementing a new surgical technique is the learning curve (LC) (Naspro et al., 2017). An understanding of the LC is crucial to determine how much surgical experience is required to provide reproducible outcomes (Khene et al, 2020). In aEEP, the LC tends to be steep, and according to a recent analysis, 50–60 cases were required to effectively perform enucleation; and efficient morcellation was also reported after 60 cases (Hueber & Zorn, 2013; Jeon et al., 2019; Kampantais et al., 2018; Khene et al, 2020).…”
Section: Multiple Energy Sources and Techniquesmentioning
confidence: 99%
“…An understanding of the LC is crucial to determine how much surgical experience is required to provide reproducible outcomes (Khene et al, 2020). In aEEP, the LC tends to be steep, and according to a recent analysis, 50–60 cases were required to effectively perform enucleation; and efficient morcellation was also reported after 60 cases (Hueber & Zorn, 2013; Jeon et al., 2019; Kampantais et al., 2018; Khene et al, 2020). Some institutions have discontinued the technique due to complications encountered early in the LC (Shigemura et al., 2017).…”
Section: Multiple Energy Sources and Techniquesmentioning
confidence: 99%
“…In a large multicentre retrospective study ( n = 922) of the first patients treated with GreenLEP by six surgeons, the post‐operative complications reported by Khene et al were found in 6.18% of the cases (4.88% were minor complications and only 1.3% major complications). Regarding functional results, SUI at 3 months was observed in 5.75% (Khene et al, 2020).…”
Section: Complicationsmentioning
confidence: 99%